Perjuangan Barisan Pemberontakan Republik Indonesia Kalimantan (BPRIK) dalam Mempertahankan Kemerdekaan di Banjarmasin - Rusdi Effendi (Prabayaksa: Journal of History Education, 2025)
This research examines the dynamics of the struggle of the Barisan Pemberakan Republik Indonesia Kalimantan (BPRIK) in defending independence in Banjarmasin during the 1945 power transition. The problems studied include the ex-political conditions of South Kalimantan during the transition of power from Japan to NICA-Dutch, the strategy and tactics of BPRIK in facing NICA forces, and the impact of the events of November 9, 1945 on the subsequent struggle for independence. The research objective is to analyze the strategic role of BPRIK in maintaining the spirit of independence through armed resistance as required by the political situation at that time. The research method uses historical method through the stages of heuristics, criticism, interpretation, and historiography by utilizing primary and secondary sources in the form of official documents, personal records, interview results, and historical literature. The results showed that the complex conditions of the ex-polises with economic collapse, social traumatization, and political uncertainty encouraged the formation of BPRIK as an alternative to armed resistance. BPRIK used an open resistance strategy with frontal attacks during the day to demonstrate legitimacy as freedom fighters, despite tactical defeats. The events of November 9, 1945 had a significant impact by strengthening community solidarity and inspiring continued struggle until South Kalimantan joined the Republic of Indonesia in 1950